Java for bioinformatics and biomedical applications - Bal, Harshawardhan (Springer, 2007)
"The science and practice of medicine has undergone a fundamental change as a result of large-scale genome projects that led to the sequencing of a number of important microbial, plant and animal genomes in the last 5 years. This book aims to combine industry standard software engineering and design principles, genomics and bioinformatics and cancer research. It focuses on creating and integrating practical, useful tools for the scientific community in the context of real-life, real-value biomedical problems that researchers face on a routine basis, rather than being just a didactic exercise in learning a programming platform. The book leverages technologies for molecular biology, genomics and bioinformatics and cancer research developed by the NIH, NCI-Center for Bioinformatics (NCICB), the National Center for Biotechnology Information (NCBI, a division of the National Library of Medicine (NLM) at the NIH) and Stanford University."--Publisher.